Risk Management in Intelligent Manufacturing Systems Using Bayesian Analysis - Miczka, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The article presents the range of modern methods used to forecast and conduct risk analysis of the production process and the characteristics of the measurements taken during the steel production process. The methodology is based on the state space representation of a dynamic system and Bayesian inference. The methodology enables us to reject the assumption of constant estimated parameters, analyse the statistical distribution of the whole and take into account a priori information, which is to say outside the dataset. The article is a review and the basis for further studies that include implementation of the concept of intelligent manufacturing in Polish industrial enterprises.